1987
DOI: 10.1029/jc092ic10p10807
|View full text |Cite
|
Sign up to set email alerts
|

The strait surface outflow

Abstract: A three-dimensional, primitive equation model is used to simulate the flow through a narrow strait. The flow within a strait has a simple two-layered structure with the interface located approximately at the middepth. However, the flow experiences a sharp transition at the strait's exit: the flow jumps from a subcritical velocity inside the strait to a supercritical velocity immediately outside the strait. Correspondingly, the density interface also slopes sharply upward to the surface. After exiting the strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…As the buoyant plume moves southward, the density interface becomes shallower, and the plume will acquire anticyclonic vorticity. This process is clearly illustrated in a numerical model study of buoyant flow from estuaries and straits [Wang, 1987]. Houghton et al [1986] also found a tongue of shelf water turning anticyclonically near the shelf break in the Mid-Atlantic Bight.…”
Section: This Remarkable Consistency Is Clear Evidence Of the Thermohmentioning
confidence: 85%
“…As the buoyant plume moves southward, the density interface becomes shallower, and the plume will acquire anticyclonic vorticity. This process is clearly illustrated in a numerical model study of buoyant flow from estuaries and straits [Wang, 1987]. Houghton et al [1986] also found a tongue of shelf water turning anticyclonically near the shelf break in the Mid-Atlantic Bight.…”
Section: This Remarkable Consistency Is Clear Evidence Of the Thermohmentioning
confidence: 85%
“…If U and f are constant and f> 0, the jet follows a circular clockwise (inertial) path with radius U/f If U decreases along the jet path as a result of entrainment, R will decrease, and an inertial spiral will result. Some support for such an inertial path is provided by numerical calculations [Wang, 1987], shown in Figure 6, and experiment [e.g., Flierl et al, 1983]. In Wang's case, -U/f--8 km, which is to be compared with -10 km, an approximately estimated value for R from Figure 6.…”
Section: For This Period a Solid Circle Indicates That A Satellite mentioning
confidence: 98%
“…Table 1 for this study are rather approximate because of mixing that occurs before the surface layer leaves the strait. Wang [1987] also adapted a three-dimensional primitive equation model, with simplified geometry, to consider both momentum and buoyancy effects. The relative vorticity was negative because of upward motion in the adjustment process.…”
Section: Introductionmentioning
confidence: 99%